(untitled) (Journal of the College of Basic Education, 2022)
The study investigates (tactile technology and its effect in the design of the industrial product)The subject of modern product designs in which tactile technology is employed, which is one of the main pillars in product design at the present time, which has contributed to clear changes in the visual output in the design system. The first credit included the research problem represented in the role of tactile technology as an effective act in the overall design output and what is its effectiveness with the recipient as a functional element, leading to its goal in defining the methods of tactile technology as an influential act in the design of the industrial product.The limits of the study included modern electronic devices with touch technology produced during the years 2010-2011.The study consisted of four chapters. The first chapter deals with the research problem, its importance, objectives, limits, and terminology. The second chapter contains the theoretical framework and a set of indicators.